Immunohistochemical Expression and Clinical Significance of Suggested Stem Cell Markers in Hepatocellular Carcinoma - Jong Jin Sung; Sang Jae Noh; Jun Sang Bae; Ho Sung Park; Kyu Yun Jang; Myoung Ja Chung; Woo Sung Moon (Korean Society of Pathologists & the Korean Society for Cytopathology, 2016)
Background: Increasing evidence has shown that tumor initiation and growth are nourished by a small subpopulation of cancer stem cells (CSCs) within the tumor mass. CSCs are posited to be responsible for tumor maintenance, growth, distant metastasis, and relapse after curative operation. We examined the expression of CSC markers in paraffin-embedded tissue sections of hepatocellular carcinoma (HCC) and correlated the results with clinicopathologic characteristics. Methods: Immunohistochemical staining for the markers believed to be expressed in the CSCs, including epithelial cell adhesion molecule (EpCAM), keratin 19 (K19), CD133, and CD56, was performed in 82 HCC specimens. Results: EpCAM expression was observed in 56% of the HCCs (46/82) and K19 in 6% (5/82). EpCAM expression in HCC significantly correlated with elevated α-fetoprotein level, microvessel invasion of tumor cells, and high histologic grade. In addition, EpCAM expression significantly correlated with K19 expression. The overall survival and relapsefree survival rates in patients with EpCAM-expressing HCC were relatively lower than those in patients with EpCAM-negative HCC. All but two of the 82 HCCs were negative for CD133 and CD56, respectively. Conclusions: Our results suggest that HCCs expressing EpCAM are associated with unfavorable prognostic factors and have a more aggressive clinical course than those not expressing EpCAM. Further, the expression of either CD133 or CD56 in paraffin-embedded HCC tissues appears to be rare.